FUNGSI PENGAWASAN BADAN PERMUSYAWARATAN DESA TERHADAP PENYELENGGARAAN PEMERINTAHAN DESA DANAU PANGGANG KECAMATAN DANAU PANGGANG KABUPATEN HULU SUNGAI UTARA KALIMANTAN SELATAN - Asma Vikra, zulfa (Universitas Panca Marga, 2025)
This study aims to examine the implementation of thesupervision of the BPD on the running of the village government in Danau Panggang Village, Hulu Sungai Utara Regency, South Kalimantan. With a descriptive-analytical approach descriptive-analytical approach, this research relies on primary data from interviews with members of the BPD as well as secondary data in the form of laws and regulations. With BPD members as well as secondary data in the form of laws and regulations and related literature. related literature. The results show that supervision by the BPD is still limited to aspects of village governance and development, while the dimensions of community development and empowerment have not been maximized. and empowerment dimensions have not been implemented optimally. The main obstacles include the lack of coordination between the BPD and the village head, BPD members' low understanding of the supervisory function, and the lack of community involvement. community involvement. Therefore, efforts are needed to strengthen capacity of the BPD and increase community participation to create more effective supervision, supporting transparent village governance, accountable, and focused on community welfare. Keyword: Supervision, BPD, Village Government